A production process of metal composite material

Through the ball milling and sintering process of modified carbon nanotubes and modified graphene and metal powder, a three-dimensional bridge structure is formed, which solves the problem of poor conductivity of existing metal composite materials and achieves improvements in mechanical properties and electrical conductivity.

CN119753407APending Publication Date: 2025-04-04SHENZHEN XINYUE NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510012755.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The electrical conductivity of existing metal composite materials is poor, which affects their functional applications.

Method used

Using a production process of metal composite materials, a three-dimensional bridge structure is formed by ball milling and sintering of modified carbon nanotubes and modified graphene with metal powder, which jointly strengthens the mechanical properties of metal composite materials and improves its conductivity.

Benefits of technology

It has achieved the simultaneous improvement of the mechanical properties and electrical conductivity of metal composite materials, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of composite material development, and in particular to a production process of a metal composite material, comprising a metal composite A, a metal composite B and metal powder, wherein the metal composite A is prepared from modified carbon nanotubes and copper nitrate, and the metal composite B is prepared from modified graphene and copper nitrate, the modified carbon nanotubes in the metal composite A can overcome the adsorption effect of van der Waals force between carbon materials and reduce agglomeration; the modified graphene in the metal composite B is prepared from graphene oxide and a silane coupling agent, can form a chemical bond with the metal powder, enhance the bonding strength of the two, and at the same time make the metal powder more evenly dispersed in a metal matrix and reduce agglomeration; the modified carbon nanotubes and the modified graphene can be combined through a π-π bond between the two, thereby synergistically strengthening the mechanical properties and electrical conductivity of the metal composite material, and the metal composite material has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite material development, in particular to a production process of a metal composite material. Background Art

[0002] Copper, aluminum, silver and other metals and some of their alloys are widely used in aerospace, transportation, construction engineering, electronic and electrical engineering, machinery manufacturing and many other fields due to their advantages of corrosion resistance, electrical conductivity, thermal conductivity and good processing performance. With the rapid development of modern industry, the above fields have put forward higher and higher requirements on the specific strength, specific stiffness, fatigue resistance, electrical conductivity, thermal conductivity, thermal expansion and other properties of these metal materials. The composite of metal materials has become an effective way to meet this development trend.

[0003] In the existing technology, adding carbon nanotubes to metal matrices such as copper, aluminum, and silver can significantly improve the strength, hardness, and wear resistance of the metal materials. However, due to the poor wettability between the carbon nanotubes and the metal matrix, the interface resistance between the two is high, and the conductivity of the composite material is much lower than that of the metal matrix, which affects the functional application of these materials.

[0004] Patent document CN111979437A discloses a metal / carbon nanotube composite material and a preparation method thereof, the preparation method comprising the following steps: preparing modified nanocellulose: mechanically mixing the modified nanocellulose, metal particles and carbon nanotubes in water to prepare a suspension: depositing the suspension, drying and heating to decompose the modified nanocellulose to obtain an intermediate product, sintering the intermediate product to obtain a metal / carbon nanotube composite material. The obtained metal / carbon nanotube composite material has good mechanical properties, but the conductivity of the composite material is poor.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a production process of metal composite materials. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a production process of a metal composite material to solve the problem of poor electrical conductivity of the metal composite material in the prior art.

[0007] Based on the above purpose, the present invention provides a production process of a metal composite material.

[0008] A production process of a metal composite material comprises the following steps: Step A1: mixing the metal composite A with the metal powder, ball milling, sintering at 750-800° C. for 1-1.5 h at a sintering pressure of 35-40 MPa, and then sintering at 900-950° C. for 1.5-3 h to obtain a sintered composite A; Step A2: mixing the metal composite B with the metal powder, ball milling, sintering at 750-800° C. for 1-1.5 h at a sintering pressure of 35-40 MPa, and then sintering at 900-950° C. for 1.5-3 h to obtain a sintered composite B; Step A3: ball-milling the sintered composite A, the sintered composite B and the metal powder, and sintering at 900-950° C. for 1.5-3 h to obtain a metal composite material; The metal powder is copper powder; The metal complex A in step A1 is prepared from modified carbon nanotubes and copper nitrate; The modified carbon nanotubes are prepared from carboxylated carbon nanotubes and polyethylene glycol; The metal complex B in step A2 is prepared from modified graphene and copper nitrate; The modified graphene is prepared from graphene oxide and a silane coupling agent.

[0009] Preferably, in step A1, the mass ratio of the metal composite A to the metal powder is 10-12:30-35; In step A2, the mass ratio of the metal composite B to the metal powder is 10-12:30-35; In step A3, the mass ratio of the sintered composite A, the sintered composite B and the metal powder is 20-30:10-15:300-320.

[0010] Preferably, the preparation method of the metal complex A is as follows: Step B1: adding the carboxylated carbon nanotubes to thionyl chloride, ultrasonicating at room temperature for 0.5-1h, raising the temperature to 60-70°C, reflux for 10-12h, cooling to room temperature, drying, adding to polyethylene glycol, reacting at 100-120°C for 20-25h, filtering, washing, and drying to obtain modified carbon nanotubes; Step B2: adding the modified carbon nanotubes into deionized water, stirring for 15-30 minutes and then ultrasonically shaking for 1-3 hours to obtain a modified carbon nanotube dispersion; Step B3: dissolving copper nitrate in deionized water, pouring into the modified carbon nanotube dispersion, stirring for 30-35 minutes, adding sodium hydroxide solution dropwise until the pH of the solution is 10-11, then adding hydrazine hydrate dropwise, placing the solution in a 85-95° C. water bath for hydrothermal reduction reaction for 1-1.5 hours, and after the solution is cooled to room temperature, removing the supernatant to obtain a precipitated complex A; Step B4: The precipitated complex A is centrifuged at 8000-8500 rpm using deionized water in a high-speed centrifuge until the pH reaches 7, and then freeze-dried for 20-25 hours to obtain a metal complex A.

[0011] Preferably, the usage ratio of the carboxylated carbon nanotubes, thionyl chloride and polyethylene glycol in step B1 is 1-1.5 g: 200-220 mL: 150-180 mL.

[0012] Preferably, the usage ratio of the modified carbon nanotubes and deionized water in step B2 is 45-50 mg: 950-1000 mL.

[0013] Preferably, the usage ratio of copper nitrate, deionized water, modified carbon nanotube dispersion and hydrazine hydrate in step B3 is 0.5-0.8 g: 18-22 mL: 95-100 mL: 8-10 mL; The concentration of the sodium hydroxide solution in step B3 is 0.2-0.5 mol / L.

[0014] Preferably, the preparation method of the metal complex B is as follows: Step C1: under nitrogen protection, adding graphene oxide to methanol and ethanol, stirring at 50-60° C. for 25-30 min, adding a silane coupling agent dropwise, heating to 90-95° C. and keeping the temperature for 12-14 h, cooling to 50-60° C., adding a ferrous sulfate reducing agent, heating to 100-120° C., washing, and centrifugation drying to obtain modified graphene; Step C2: adding the modified graphene to deionized water, stirring for 15-30 minutes and then ultrasonically shaking for 1-3 hours to obtain a modified graphene dispersion; Step C3: dissolving copper nitrate in deionized water, pouring into the modified graphene dispersion, stirring for 30-35 minutes, adding sodium hydroxide solution dropwise until the pH of the solution is 10-11, then adding hydrazine hydrate dropwise, placing the solution in a 85-95° C. water bath for hydrothermal reduction reaction for 1-1.5 hours, and after the solution is cooled to room temperature, removing the supernatant to obtain a precipitated complex B; Step C4: The precipitated complex B is centrifuged at 8000-8500 rpm using deionized water in a high-speed centrifuge until the pH reaches 7, and then freeze-dried for 20-25 hours to obtain the metal complex B.

[0015] Preferably, the mass ratio of graphene oxide, methanol, ethanol, silane coupling agent and ferrous sulfate reducing agent in step C1 is 3-5: 240-250: 200-210: 220-230: 180-190.

[0016] Preferably, the usage ratio of the modified graphene and deionized water in step C2 is 45-50 mg:95-100 mL.

[0017] Preferably, the usage ratio of the copper nitrate, deionized water, modified graphene dispersion and hydrazine hydrate in step C3 is 0.5-0.8 g: 18-22 mL: 95-100 mL: 8-10 mL; The concentration of the sodium hydroxide solution in step C3 is 0.2-0.5 mol / L.

[0018] Beneficial effects of the present invention: The present invention provides a production process of a metal composite material, comprising a metal composite A, a metal composite B and a metal powder, wherein the metal composite A and the metal composite B are respectively subjected to ball milling and sintering with the metal powder, and the two prepared products are subjected to ball milling and sintering with the metal powder again; wherein the metal composite A is prepared from modified carbon nanotubes and copper nitrate, and the metal composite B is prepared from modified graphene and copper nitrate, and the modified carbon nanotubes and the modified graphene can be combined through a π-π bond therebetween to form a three-dimensional bridging structure, thereby synergistically strengthening the mechanical properties of the metal composite material; The modified carbon nanotubes in the metal composite A are prepared from carboxylated carbon nanotubes and polyethylene glycol, so that oxygen-containing groups are grafted on the surface of the carbon nanotubes. The presence of these oxygen-containing groups can overcome the adsorption effect of the van der Waals force between carbon materials, reduce agglomeration, and improve the electrical conductivity of the mechanical properties of the metal composite material; the modified graphene in the metal composite B is prepared from graphene oxide and a silane coupling agent, and can form a chemical bond with the metal powder, which helps to overcome the interface mismatch problem between the metal and the carbon-based material, enhance the bonding strength between the two, and at the same time make it more evenly dispersed in the metal matrix, reduce agglomeration, improve the mechanical properties and electrical conductivity of the metal composite material, and has broad application prospects. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0020] The sources and properties of some of the raw materials used in the present invention are as follows: Carboxylated carbon nanotubes were purchased from Xi’an Qiyue Biotechnology Co., Ltd.; polyethylene glycol model was PEG-200, purchased from Hangzhou Electrochemical Group Additive Chemical Co., Ltd.; graphene oxide was purchased from Zhejiang Yamei Nanotechnology Co., Ltd.; silane coupling agent was KH550, purchased from Jinan Shanhai Chemical Technology Co., Ltd.; ferrous sulfate reducing agent was purchased from Guangzhou Tianjia Biotechnology Co., Ltd.

[0021] Embodiment 1: A production process of a metal composite material, comprising the following steps: S1. Add 1 g of carboxylated carbon nanotubes to 2 mL of thionyl chloride, ultrasonicate at room temperature for 0.5 h, raise the temperature to 60 ° C, reflux for 10 h, cool to room temperature, dry, add to 150 mL of polyethylene glycol, react at 100 ° C for 20 h, filter, wash, and dry to obtain modified carbon nanotubes; S2. 45 mg of modified carbon nanotubes were added to 950 mL of deionized water, stirred for 15 min and then ultrasonically vibrated for 1 h to obtain a modified carbon nanotube dispersion; S3. Take 0.5g of copper nitrate and dissolve it in 18mL of deionized water, pour it into 95mL of modified carbon nanotube dispersion, stir for 30min, add 0.2mol / L sodium hydroxide solution until the pH of the solution is 10, then add 8mL of hydrazine hydrate, put it into a 85℃ water bath for hydrothermal reduction reaction for 1h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex A; S4. The precipitated complex A was centrifuged at 8000 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 20 h to obtain a metal complex A; S5. Under nitrogen protection, 3 g of graphene oxide was added to 240 g of methanol and 200 g of ethanol, stirred at 50 ° C for 25 min, 220 g of silane coupling agent KH550 was added dropwise, and the temperature was raised to 90 ° C for 12 h. After cooling to 50 ° C, 180 g of ferrous sulfate reducing agent was added, and the temperature was raised to 100 ° C, washed, and centrifuged to obtain modified graphene; S6. 45 mg of modified graphene was added to 95 mL of deionized water, stirred for 15 min, and then ultrasonically vibrated for 1 h to obtain a modified graphene dispersion; S7. Take 0.5g of copper nitrate and dissolve it in 18mL of deionized water, pour it into 95mL of modified graphene dispersion, stir for 30min, add 0.2mol / L sodium hydroxide solution until the pH of the solution is 10, then add 8mL of hydrazine hydrate, put it into a 85℃ water bath for hydrothermal reduction reaction for 1h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex B; S8. The precipitated complex B was centrifuged at 8000 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 20 h to obtain a metal complex B; S9. 10 g of metal composite A was mixed with 30 g of copper powder, ball-milled, and sintered at 750° C. for 1 h under a sintering pressure of 35 MPa to obtain a sintered composite A, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1000 r / min, the ball-milling time was 10 h, and the ball-to-material ratio was 8:1; S10. 10 g of metal composite B was mixed with 30 g of copper powder, ball-milled, and sintered at 750° C. for 1 h under a sintering pressure of 35 MPa to obtain a sintered composite B, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1000 r / min, the ball-milling time was 10 h, and the ball-to-material ratio was 8:1; S11. After ball milling 20 g of sintered composite A, 10 g of sintered composite B and 300 g of copper powder, sintering at 900°C for 1.5 h to obtain a metal composite material, wherein the ball milling atmosphere is argon atmosphere, the ball milling speed is 400 r / min, the ball milling time is 3 h, and the ball-to-material ratio is 4:1.

[0022] Embodiment 2: A production process of a metal composite material, comprising the following steps: S1. Add 1.2 g of carboxylated carbon nanotubes to 205 mL of thionyl chloride, ultrasonicate at room temperature for 0.6 h, raise the temperature to 64 ° C, reflux for 10.5 h, cool to room temperature, dry, add to 160 mL of polyethylene glycol, react at 105 ° C for 22 h, filter, wash, and dry to obtain modified carbon nanotubes; S2. 46 mg of modified carbon nanotubes were added to 960 mL of deionized water, stirred for 20 min, and then ultrasonically vibrated for 1.5 h to obtain a modified carbon nanotube dispersion; S3. Take 0.6g of copper nitrate and dissolve it in 19mL of deionized water, pour it into 96mL of modified carbon nanotube dispersion, stir for 32min, add 0.3mol / L sodium hydroxide solution until the pH of the solution is 10, then add 8.5mL of hydrazine hydrate, put it into a 90℃ water bath for hydrothermal reduction reaction for 1.2h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex A; S4. The precipitated complex A was centrifuged at 8200 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 22 hours to obtain a metal complex A; S5. Under nitrogen protection, 3.5 g of graphene oxide was added to 244 g of methanol and 204 g of ethanol, stirred at 54 ° C for 26 min, 224 g of silane coupling agent KH550 was added dropwise, the temperature was raised to 92 ° C and kept for 12.5 h, the temperature was lowered to 54 ° C, 184 g of ferrous sulfate reducing agent was added, the temperature was raised to 100-120 ° C, washed, and centrifuged to obtain modified graphene; S6. 46 mg of modified graphene was added to 96 mL of deionized water, stirred for 20 min, and then ultrasonically vibrated for 1.5 h to obtain a modified graphene dispersion; S7. Take 0.6g of copper nitrate and dissolve it in 19mL of deionized water, pour it into 96mL of modified graphene dispersion, stir for 32min, add 0.3mol / L sodium hydroxide solution until the pH of the solution is 10, then add 8.5mL of hydrazine hydrate, put it into a 90℃ water bath for hydrothermal reduction reaction for 1.2h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex B; S8. The precipitated complex B was centrifuged at 8200 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 22 hours to obtain a metal complex B; S9. 10.5 g of metal composite A was mixed with 32 g of copper powder, ball-milled, and sintered at 760° C. for 1.2 h under a sintering pressure of 36 MPa to obtain a sintered composite A, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1200 r / min, the ball-milling time was 10.5 h, and the ball-to-material ratio was 8:1; S10. 10.5 g of metal composite B was mixed with 32 g of copper powder, ball-milled, and sintered at 760° C. for 1.2 h under a sintering pressure of 36 MPa to obtain a sintered composite B, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1200 r / min, the ball-milling time was 10.5 h, and the ball-to-material ratio was 8:1; S11. After ball milling 24 g of sintered composite A, 12 g of sintered composite B and 310 g of copper powder, the mixture was sintered at 920° C. for 2 h to obtain a metal composite material, wherein the ball milling atmosphere was argon atmosphere, the ball milling speed was 500 r / min, the ball milling time was 3.5 h, and the ball-to-material ratio was 4:1.

[0023] Embodiment 3: A production process of a metal composite material, comprising the following steps: S1. Add 1.4 g of carboxylated carbon nanotubes to 215 mL of thionyl chloride, ultrasonicate at room temperature for 0.8 h, raise the temperature to 68 ° C, reflux for 11 h, cool to room temperature, dry, add to 170 mL of polyethylene glycol, react at 115 ° C for 24 h, filter, wash, and dry to obtain modified carbon nanotubes; S2. 48 mg of modified carbon nanotubes were added to 980 mL of deionized water, stirred for 28 min, and then ultrasonically vibrated for 2 h to obtain a modified carbon nanotube dispersion; S3. Take 0.7g of copper nitrate and dissolve it in 21mL of deionized water, pour it into 98mL of modified carbon nanotube dispersion, stir for 34min, add 0.4mol / L sodium hydroxide solution until the pH of the solution is 11, then add 9mL of hydrazine hydrate, put it into a 92℃ water bath for hydrothermal reduction reaction for 1.4h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex A; S4. The precipitated complex A was centrifuged at 8400 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 24 hours to obtain a metal complex A; S5. Under nitrogen protection, 4 g of graphene oxide was added to 248 g of methanol and 208 g of ethanol, stirred at 58 ° C for 28 min, 228 g of silane coupling agent KH550 was added dropwise, the temperature was raised to 94 ° C for 13 h, the temperature was lowered to 58 ° C, 188 g of ferrous sulfate reducing agent was added, the temperature was raised to 115 ° C, washed, and centrifuged to obtain modified graphene; S6. 48 mg of modified graphene was added to 98 mL of deionized water, stirred for 28 min, and then ultrasonically vibrated for 2 h to obtain a modified graphene dispersion; S7. Take 0.7g of copper nitrate and dissolve it in 21mL of deionized water, pour it into 98mL of modified graphene dispersion, stir for 34min, add 0.4mol / L sodium hydroxide solution until the pH of the solution is 11, then add 9mL of hydrazine hydrate, put it into a 92℃ water bath for hydrothermal reduction reaction for 1.4h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex B; S8. The precipitated complex B was centrifuged at 8400 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 24 hours to obtain a metal complex B; S9. 11 g of metal composite A was mixed with 34 g of copper powder, ball-milled, and sintered at 780° C. for 1.4 h under a sintering pressure of 38 MPa to obtain a sintered composite A, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1400 r / min, the ball-milling time was 11 h, and the ball-to-material ratio was 9:1; S10. 11 g of metal composite B was mixed with 34 g of copper powder, ball-milled, and sintered at 780° C. for 1.4 h under a sintering pressure of 38 MPa to obtain a sintered composite B, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1400 r / min, the ball-milling time was 11 h, and the ball-to-material ratio was 9:1; S11. After ball milling 28 g of sintered composite A, 14 g of sintered composite B and 315 g of copper powder, the mixture was sintered at 940°C for 2.5 h to obtain a metal composite material, wherein the ball milling atmosphere was argon atmosphere, the ball milling speed was 700 r / min, the ball milling time was 4 h, and the ball-to-material ratio was 5:1.

[0024] Embodiment 4: A production process of a metal composite material, comprising the following steps: S1. Add 1.5 g of carboxylated carbon nanotubes to 220 mL of thionyl chloride, ultrasonicate at room temperature for 1 h, raise the temperature to 70 ° C, reflux for 12 h, cool to room temperature, dry, add to 180 mL of polyethylene glycol, react at 120 ° C for 25 h, filter, wash, and dry to obtain modified carbon nanotubes; S2. 50 mg of modified carbon nanotubes were added to 1000 mL of deionized water, stirred for 30 min and then ultrasonically vibrated for 3 h to obtain a modified carbon nanotube dispersion; S3. Take 0.8g of copper nitrate and dissolve it in 22mL of deionized water, pour it into 100mL of modified carbon nanotube dispersion, stir for 35min, add 0.5mol / L sodium hydroxide solution until the pH of the solution is 11, then add 10mL of hydrazine hydrate, put it into a 95℃ water bath for hydrothermal reduction reaction for 1.5h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex A; S4. The precipitated complex A was centrifuged at 8500 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 25 h to obtain a metal complex A; S5. Under nitrogen protection, 5 g of graphene oxide was added to 250 g of methanol and 210 g of ethanol, stirred at 60 ° C for 30 min, 230 g of silane coupling agent KH550 was added dropwise, the temperature was raised to 95 ° C and kept for 14 h, the temperature was lowered to 60 ° C, 190 g of ferrous sulfate reducing agent was added, the temperature was raised to 120 ° C, washed, and centrifuged to obtain modified graphene; S6. 50 mg of modified graphene was added to 100 mL of deionized water, stirred for 30 min, and then ultrasonically vibrated for 3 h to obtain a modified graphene dispersion; S7. Take 0.8g of copper nitrate and dissolve it in 22mL of deionized water, pour it into 100mL of modified graphene dispersion, stir for 35min, add 0.5mol / L sodium hydroxide solution until the pH of the solution is 11, then add 10mL of hydrazine hydrate, put it into a 95℃ water bath for hydrothermal reduction reaction for 1.5h, and after the solution is cooled to room temperature, remove the supernatant to obtain precipitated complex B; S8. The precipitated complex B was centrifuged at 8500 rpm in a high-speed centrifuge using deionized water until the pH reached 7, and then freeze-dried for 25 h to obtain a metal complex B; S9. 12 g of metal composite A was mixed with 35 g of copper powder, ball-milled, and sintered at 800° C. for 1.5 h under a sintering pressure of 40 MPa to obtain a sintered composite A, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1500 r / min, the ball-milling time was 12 h, and the ball-to-material ratio was 9:1; S10. 12 g of metal composite B was mixed with 35 g of copper powder, ball-milled, and sintered at 800° C. for 1.5 h under a sintering pressure of 40 MPa to obtain a sintered composite B, wherein the ball-milling atmosphere was an argon atmosphere, the ball-milling speed was 1500 r / min, the ball-milling time was 12 h, and the ball-to-material ratio was 9:1; S11. After ball milling 30 g of sintered composite A, 15 g of sintered composite B and 320 g of copper powder, sintering at 950° C. for 3 h to obtain a metal composite material, wherein the ball milling atmosphere is argon atmosphere, the ball milling speed is 800 r / min, the ball milling time is 5 h, and the ball-to-material ratio is 5:1.

[0025] Comparative Example 1: Compared with Example 1, the metal composite material in this comparative example is not added with the metal composite material A during the preparation process of the metal composite material, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the metal composite material is obtained.

[0026] Comparative Example 2: Compared with Example 1, the metal composite material in this comparative example is not added with the metal composite material B during the preparation process of the metal composite material, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the metal composite material is obtained.

[0027] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "modified carbon nanotubes" with "carboxylated carbon nanotubes", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a metal composite material is obtained.

[0028] Comparative Example 4: Compared with Example 1, this comparative example only replaces "modified graphene" with "graphene oxide", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a metal composite material is obtained.

[0029] Comparative Example 5: Compared with Example 1, this comparative example only replaces "20g sintered composite A, 10g sintered composite B and 300g copper powder" with "100g sintered composite A, 200g sintered composite B and 300g copper powder", and the remaining steps and parameters are the same and will not be repeated in this comparative example to finally obtain a metal composite material.

[0030] Performance Testing: Density test: The density of the metal composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 5 was tested using the principle of Archimedes drainage method. The mass of the metal composite materials exposed to air and the mass in water after peeling were measured in turn on a high-precision electronic balance, and the density of the sample was calculated according to the following formula: The density calculation formula is: ; where ρ 水 The density of distilled water during the test, in g / cm 3 ; m1 is the mass of the metal composite material in air, in g; m2 is the mass of the metal composite material in water, in g.

[0031] Conductivity test: The conductivity of the metal composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 5 was tested using a FOR-7501 eddy current conductivity meter. In order to ensure perfect contact between the contact probe and the sample to eliminate measurement errors during measurement, the tested composite materials were polished to make the sample surface flat. At the same time, in order to ensure the accuracy of the test, the metal composite material was tested at 5 different positions to obtain the average value. The relative conductivity (%IACS) of the composite material can be obtained by dividing the measured conductivity of the composite material with the conductivity of the international annealed copper as 100%IACS (the international annealed copper standard is 58MS / m).

[0032] The relative conductivity calculation formula is: ; Where σ is the electrical conductivity of the metal composite material being tested, in units of MS / m.

[0033] Hardness test: The Vickers hardness of the metal composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 5 was tested using an electric Brinell hardness tester of model HBRV-187.5, with a load of 30 kg and a load time of 30 seconds. The diagonal length of each indentation was then measured under a microscope using computer software, and 5 different positions were tested and the average value was taken.

[0034] The Vickers hardness calculation formula is: ; Where HV is the Vickers hardness; F is the test force, in N; d is the arithmetic mean of the two diagonals of the indentation d1 and d2, in nm.

[0035] Tensile properties: The room temperature tensile properties of the composite material were tested using a WDW-20 electronic universal testing machine at a tensile rate of 0.5 mm / min. The metal composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 5 were cut into samples with a length of 20 mm, a gauge length of 10 mm, and a cross section of 2 mm×2 mm, with a tolerance range of ±0.05 mm. Before the tensile test, the surface oxide layer of the plate was polished with 2000-grit sandpaper to make its surface smooth. To ensure the accuracy of the experiment, the same composite material was subjected to three tensile tests.

[0036] Table 1

[0037] Data Analysis: It can be seen from Table 1 that the metal composite material prepared by the present invention has more excellent mechanical properties and electrical conductivity; This may be because the modified carbon nanotubes in the metal composite A of the present invention are prepared from carboxylation carbon nanotubes and polyethylene glycol, so that oxygen-containing groups are grafted on the surface of the carbon nanotubes. The presence of these oxygen-containing groups can overcome the adsorption effect of the van der Waals force between carbon materials, reduce agglomeration, and improve the electrical conductivity of the mechanical properties of the metal composite material. However, when the carboxylation carbon nanotubes are combined with the metal surface, the effective conductive path of the carbon nanotubes may be reduced, so that the electrical conductivity of the metal composite material will not be significantly improved. The carbon nanotubes modified by polyethylene glycol have good dispersibility and help to form a more uniform conductive network. The modified graphene in the metal composite B is prepared from graphene oxide and a silane coupling agent, and can form a chemical bond with the metal powder, which helps to overcome the interface mismatch problem between the metal and the carbon-based material, enhance the bonding strength between the two, and at the same time make it more evenly dispersed in the metal matrix and reduce agglomeration. However, the graphene oxide has not been fully reduced, which may hinder the free flow of electrons, and its electrical conductivity when combined with the metal may indeed be poor. The metal composite A in the present invention is prepared from modified carbon nanotubes and copper nitrate, and the metal composite B is prepared from modified graphene and copper nitrate. The modified carbon nanotubes and the modified graphene can be combined through the π-π bond between the two to form a three-dimensional bridging structure, thereby synergistically strengthening the mechanical properties of the metal composite material. The present invention further regulates the usage ratio of the metal composite A, the metal composite B and the metal powder, and selects a specific ratio with the most stable effect and the highest utilization rate of the effective ingredients for compounding; Therefore, the metal composite material prepared by the present invention has excellent mechanical properties and its electrical conductivity is also improved accordingly.

[0038] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0039] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A production process of a metal composite material, characterized in that: The following steps are involved: Step A1: mixing the metal composite A with the metal powder, ball milling, sintering at 750-800° C. for 1-1.5 h at a sintering pressure of 35-40 MPa, and then sintering at 900-950° C. for 1.5-3 h to obtain a sintered composite A; Step A2: mixing the metal composite B with the metal powder, ball milling, sintering at 750-800° C. for 1-1.5 h at a sintering pressure of 35-40 MPa, and then sintering at 900-950° C. for 1.5-3 h to obtain a sintered composite B; Step A3: ball-milling the sintered composite A, the sintered composite B and the metal powder, and sintering at 900-950° C. for 1.5-3 h to obtain a metal composite material; The metal powder is copper powder; The metal complex A in step A1 is prepared from modified carbon nanotubes and copper nitrate; The modified carbon nanotubes are prepared from carboxylated carbon nanotubes and polyethylene glycol; The metal complex B in step A2 is prepared from modified graphene and copper nitrate; The modified graphene is prepared from graphene oxide and a silane coupling agent.

2. The production process of the metal composite material according to claim 1, characterized in that: In step A1, the mass ratio of the metal composite A to the metal powder is 10-12:30-35; In step A2, the mass ratio of the metal composite B to the metal powder is 10-12:30-35; In step A3, the mass ratio of the sintered composite A, the sintered composite B and the metal powder is 20-30:10-15:300-320.

3. The production process of the metal composite material according to claim 1, characterized in that: The preparation method of the metal complex A is as follows: Step B1: adding the carboxylated carbon nanotubes to thionyl chloride, ultrasonicating at room temperature for 0.5-1h, raising the temperature to 60-70°C, reflux for 10-12h, cooling to room temperature, drying, adding to polyethylene glycol, reacting at 100-120°C for 20-25h, filtering, washing, and drying to obtain modified carbon nanotubes; Step B2: adding the modified carbon nanotubes into deionized water, stirring for 15-30 minutes and then ultrasonically shaking for 1-3 hours to obtain a modified carbon nanotube dispersion; Step B3: dissolving copper nitrate in deionized water, pouring into the modified carbon nanotube dispersion, stirring for 30-35 minutes, adding sodium hydroxide solution dropwise until the pH of the solution is 10-11, then adding hydrazine hydrate dropwise, placing the solution in a 85-95° C. water bath for hydrothermal reduction reaction for 1-1.5 hours, and after the solution is cooled to room temperature, removing the supernatant to obtain a precipitated complex A; Step B4: The precipitated complex A is centrifuged at 8000-8500 rpm using deionized water in a high-speed centrifuge until the pH reaches 7, and then freeze-dried for 20-25 hours to obtain a metal complex A.

4. The production process of the metal composite material according to claim 3, characterized in that: The usage ratio of the carboxylated carbon nanotubes, thionyl chloride and polyethylene glycol in step B1 is 1-1.5 g: 200-220 mL: 150-180 mL. The production process of the metal composite material according to claim 3, characterized in that the dosage ratio of the modified carbon nanotubes and deionized water in step B2 is 45-50 mg: 950-1000 mL. The production process of the metal composite material according to claim 3, characterized in that the amount ratio of the copper nitrate, deionized water, modified carbon nanotube dispersion and hydrazine hydrate in step B3 is 0.5-0.8 g: 18-22 mL: 95-100 mL: 8-10 mL; The concentration of the sodium hydroxide solution in step B3 is 0.2-0.5 mol / L.

5. The production process of the metal composite material according to claim 1, characterized in that: The preparation method of the metal complex B is as follows: Step C1: under nitrogen protection, adding graphene oxide to methanol and ethanol, stirring at 50-60° C. for 25-30 min, adding a silane coupling agent dropwise, heating to 90-95° C. and keeping the temperature for 12-14 h, cooling to 50-60° C., adding a ferrous sulfate reducing agent, heating to 100-120° C., washing, and centrifugation drying to obtain modified graphene; Step C2: adding the modified graphene to deionized water, stirring for 15-30 minutes and then ultrasonically shaking for 1-3 hours to obtain a modified graphene dispersion; Step C3: dissolving copper nitrate in deionized water, pouring into the modified graphene dispersion, stirring for 30-35 minutes, adding sodium hydroxide solution dropwise until the pH of the solution is 10-11, then adding hydrazine hydrate dropwise, placing the solution in a 85-95° C. water bath for hydrothermal reduction reaction for 1-1.5 hours, and after the solution is cooled to room temperature, removing the supernatant to obtain a precipitated complex B; Step C4: The precipitated complex B is centrifuged at 8000-8500 rpm using deionized water in a high-speed centrifuge until the pH reaches 7, and then freeze-dried for 20-25 hours to obtain the metal complex B.

6. The production process of the metal composite material according to claim 7, characterized in that: The mass ratio of graphene oxide, methanol, ethanol, silane coupling agent and ferrous sulfate reducing agent in step C1 is 3-5: 240-250: 200-210: 220-230: 180-190.

7. The production process of the metal composite material according to claim 7, characterized in that: The usage ratio of the modified graphene and deionized water in step C2 is 45-50 mg: 95-100 mL.

8. The production process of the metal composite material according to claim 7, characterized in that: The amount ratio of copper nitrate, deionized water, modified graphene dispersion and hydrazine hydrate in step C3 is 0.5-0.8 g: 18-22 mL: 95-100 mL: 8-10 mL; The concentration of the sodium hydroxide solution in step C3 is 0.2-0.5 mol / L.

Citation Information

Patent Citations

  • Metal / carbon nanotube composite material and preparation method thereof

    CN111979437A